Diagnóstico de las afectaciones de la disposición final de los residuos sólidos en la actividad pesquera del sector Bajo Alto del cantón El Guabo provincia de El Oro - Arciniega Garino, Carlos Manuel; Pineda Zambrano, Nadia Andrea; Barros Cabrera, Jorge Enrique (Machala : Universidad Técnica de Machala, 2016)
The aim of the thesis project is to diagnose the effects of the disposal of solid waste in the fishing sector activity Low High Guabo Canton. The methodology was applied four phases were used: the first consisted of gathering information the same that helped us identify the improper disposal of solid waste and the current state of Bajo Alto. In the second part we proceeded to use research techniques such as surveys and interviews, which allowed us to identify the area of impact assessment for subsequent statistical analysis. In the third part according to our statistical analysis it was found that much of the artisanal fisheries sector been affected by the improper disposal of domestic solid waste the same as harm the economy of the fishing industry, which influences the reduction the death rate of the different species of most commercial fish.
Keywords: DIAGNOSTICO; RESIDUO; SOLIDO; PESQUERA